What Would a BIV Do Differently? A Pragmatist Defense of Contextualist Fallibilism - Aminzadeh Dezfuli, Abtin (The Oracle, 2021)
In “Solving the Skeptical Problem”, Keith DeRose offers a contextualist response to a possible formulation of the skeptical hypothesis about knowledge. I will here outline his position in order to demonstrate the potential in the contextualist approach to effectively solve the skeptical puzzle. I will, however, go on to argue that the contextualist response as formulated by DeRose falls short of achieving its persistently elusive goal. In this, I will follow David Lewis, in “Elusive Knowledge”, in order to explain how the type of contextualist solution offered by DeRose is inherently self-defeating. I will then suggest the introduction of a pragmatist understanding of knowledge into the contextualist picture. Shifting towards fallibilism, I will argue that in light of pragmatist considerations, the skeptical puzzle loses much, if not all, of its threatening significance.